New distribution records and range extensions for three Sumatran orchids species in Kalimantan, Borneo, Indonesia - Zainudin (Universidad de Costa Rica, 2024)
Borneo, one of the largest and most biodiverse islands in the world, continues to reveal remarkable biological discoveries. Its unique geological history and the relatively limited extent of botanical exploration have contributed to the island’s enigmatic flora. During our expedition across three provinces in the Kalimantan, Indonesia, we discovered three orchid species previously unrecorded on this mainland. Based on comprehensive specimen examination and literature review, three Sumatran orchid species, Eria compressoclavata, Oxystophyllum cuneatipetalum, and Plocoglottis quadrifolia, are reported for the first time from Kalimantan, Borneo, Indonesia. This study provides detailed morphological descriptions, notes on the expanded distributional ranges, ecological observations, and high-resolution photographic documentation for each species.